Navajo Trader - Richardson, Gladwell (Book collections on Project MUSE., 2003)
Gladwell Richardson was born on Sept. 4, 1903 in Alvarado, Texas. He divided his childhood between Oklahoma and Arizona. Gladwell was self-taught and attended two institutions of higher education. He worked on the Houck Trading Post from 1918-1920 when he joined the Marines in San Francisco and soon released because of this age. A few months later he joined the Navy with his parents consent where he served in the states and the South Pacific. After his time in the service was over he returned to help with the trading post.